The effect of trust and social presence on consumer purchase interest in B2C e-commerce in Indonesia - Aziz, Abd; Rahman, Moh. Abd; Rachman, Poppy; Lestari, Wahyu (Edelweiss Applied Science and Technology, 2024)
This study aims to examine the impact of social presence and trust dimensions, including integrity, predictability, capability, and benevolence, on consumer purchase intentions in business-to-consumer (B2C) e-commerce, with a focus on Indonesian consumers. The research employs a quantitative methodology, gathering data through validated and reliable questionnaires distributed via Google Forms to individuals who have completed transactions through e-commerce websites or applications. The data is analyzed using Structural Equation Modeling (SEM) with AMOS version 22 software. The findings indicate that social presence has a significant positive effect on trust dimensions, such as integrity, predictability, capability, and benevolence. In addition, consumer purchase intentions are significantly influenced by their trust in the vendor’s integrity, predictability, capability, and benevolence. The study suggests that e-commerce vendors can enhance their social presence by incorporating features such as personal chat options with customer service, as well as integrating multimedia elements like images, videos, or emoticons. These efforts can help create a warmer, more engaging online environment, reflecting the vendor’s capabilities and boosting consumer trust and purchase intentions.